Theoretical Evaluation of Fuel Consumption in Fishing Vessel Machinery - Yaqin, Rizqi Ilmal; Anjaska, Riski; Demeianto, Bobby; Siahaan, Juniawan Preston (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2024)
Fuel serves as a crucial element in the operations of fishing businesses employing boats. Presently, the usage of fuel in ships remains significant, yet it lacks thorough mathematical and theoretical assessment. This research aims to evaluate, both mathematically and theoretically, the fuel consumption of fishing vessels during their fishing endeavors. The study involved observations of various aspects, such as engine types, fuel types, and fuel flow, on fishing vessels. Fuel consumption was computed based on operational hours and RPM (Revolutions Per Minute) of diesel engines onboard ships. The findings revealed that engines with identical loads exhibited varying fuel consumption rates due to differences in cylinder volume. Additionally, fuel consumption increased with higher RPM. Fluctuations in fuel consumption during fishing operations were attributed to adjustments made by vessels according to environmental and situational factors. Theoretical and mathematical analyses indicated that several factors, including operational hours, RPM, and cylinder volume, influence fuel consumption in diesel engines of fishing vessels. This study's significance lies in providing insights into the theoretical and mathematical aspects of predicting fuel consumption in diesel engines utilized in fishing vessels.